ANALISIS PENGARUH KUALITAS PELAYANAN, PERSEPSI NILAI, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN DALAM MENINGKATKAN NIAT BELI ULANG (Studi pada Konsumen E-commerce Tokopedia) - Ardine Hasna Savira (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to analyze the effect of service quality, perceived value and brand image on consumer satisfaction in increasing repurchase intentions. This research was conducted due to research problems and inconsistencies in research results related to consumer satisfaction. The object used in this research is e-commerce Tokopedia. Respondent criteria in this study were someone who had made a purchase at Tokopedia and was 18 years old. The data applied in this study are primary data and secondary data. A total of 186 respondents were determined as the research sample. The analytical method of this research uses the SEM (Structural Equation Model) analysis technique from the AMOS program. Based on the analysis results prove that service quality has a positive and significant effect on consumer satisfaction variables, perceived value by consumers has a positive effect on customer satisfaction, e-commerce brand image has a positive effect on customer satisfaction, consumer satisfaction has a positive effect on repurchase intentions. Keywords : Service Quality; Perceived Value; Brand Image; Consumer Satisfaction; Repurchase Intention